Brassinosteroids regulate root meristem development by mediating BIN2-UPB1 module in Arabidopsis - Li, Taotao (PLoS Genet, 2020)
Plant steroid hormones brassinosteroids (BRs) regulate plant growth and development at many levels. While negative regulatory factors that inhibit development and are counteracted by BRs exist in the root meristem, these factors have not been characterized. The functions of UPB1 transcription factor in BR-regulated root growth have not been established, although its role in regulating root are well documented. Here, we found that BIN2 interacts with and phosphorylates the UPB1 transcription factor consequently promoting UPB1 stability and transcriptional activity. Genetic analysis revealed that UPB1 deficiency could partially recover the short-root phenotype of BR-deficient mutants. Expression of a mutated UPB1(S37AS41A) protein lacking a conserved BIN2 phosphorylation sites can rescue shorter root phenotype of bin2-1 mutant. In addition, UPB1 was repressed by BES1 at the transcriptional level. The paclobutrazol-resistant protein family (PRE2/3) interacts with UPB1 and inhibits its transcriptional activity to promote root meristem development, and BIN2-mediated phosphorylation of UPB1 suppresses its interaction with PRE2/3, and subsequently impairing root meristem development. Taken together, our data elucidate a molecular mechanism by which BR promotes root growth via inhibiting BIN2-UPB1 module.